PENGARUH STRUKTUR MODAL, UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP HARGA SAHAM SYARIAH YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX PERIODE 2015-2019 - Qolbiyati Muthmainah; Salamatun Asakdiyah; Taufik Hidayat (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to examine and analyze the effect of capital structure, firm size and profitability partially and simultaneously on Islamic stock prices. The object of research is a company listed on the Jakarta Islamic Index (JII) for the 2015-2019 period. The research method uses quantitative methods with causal research design (causality). The research sample was 12 companies for 4 years of research so that the number of observations in this study was 48 observations. The analysis technique in this study uses the IBM SPSS For Windows program with multiple linear regression models. The results showed that capital structure had an insignificant negative effect on Islamic stock prices, firm size had a positive and significant effect on Islamic stock prices, and profitability had a positive and significant effect on Islamic stock prices, and together with capital structure, firm size, and profitability. significant effect on Islamic stock prices.